Case Series: The Coexistence of Thrombocytopenia and Thromboembolism in COVID-19 Patients on ECMO: A Case Series and Literature Review - Jones, Can; Chen, Kai; Narendran, Vijay (Frontiers in Medicine, 2021)
Thrombocytopenia and thromboembolism are common complications in coronavirus disease 2019 (COVID-19) patients. The fact that COVID-19 patients develop both thrombocytopenia and thromboembolism has been observed and multiple studies have investigated the underlying pathophysiology. Extracorporeal membrane oxygenation (ECMO) is reserved for COVID-19 patients who develop respiratory failure and not respond to conventional mechanical ventilation. ECMO induces thromboembolism and raises the incidence of developing thromboembolic events in COVID-19 patients. Here we report the hospital courses and outcomes of three COVID-19 patients who were treated with ECMO, then developed both thrombocytopenia and thromboembolism. The coexistence of thrombocytopenia and thromboembolism challenges the clinical treatment strategy, including the decision of initiating anticoagulation. Based on current data, anticoagulation is recommended to all hospitalized COVID-19 patients unless there is active bleeding or platelets drop below 50,000 cells/ul. Further investigation into the mechanisms and implications of thrombocytopenia and thromboembolism in patients with COVID-19 pneumonia will lead to significantly improved outcomes and prognosis for the patients.